2021
DOI: 10.1088/1757-899x/1116/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon black and graphene on the performance of EPDM rubber composites: A short review

Abstract: Ethylene Propylene Diene Monomer (EPDM) rubber is for major used in engineering and many technical works and its application like automobile, constructions, electronic industries, and electric and many more. Industries commonly EPDM use for making the rubber inlet/outlet hoses for car and other vehicle. EPDM rubber properties are like good weather resistance ability as well as heat ozone. The resistance of steam is outstanding. EPDM rubber commonly is used for seals in automobile area. In the present review pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, it seems unlikely to attain cocrosslinking of elastomers in the presence of reactive nanofillers [1]. Ethylenepropylene diene monomer (EPDM) is an amorphous rubber widely used ranging from automotive and construction to the electronic industries, but it suffers from poor mechanical and oil resistance-necessitating the use of reinforcing agents or complementary polymers [2]. Nitrile butadiene rubber (NBR) has descent hot oil and ozone resistance [3], low-temperature flexibility [4] and appropriate mechanical properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems unlikely to attain cocrosslinking of elastomers in the presence of reactive nanofillers [1]. Ethylenepropylene diene monomer (EPDM) is an amorphous rubber widely used ranging from automotive and construction to the electronic industries, but it suffers from poor mechanical and oil resistance-necessitating the use of reinforcing agents or complementary polymers [2]. Nitrile butadiene rubber (NBR) has descent hot oil and ozone resistance [3], low-temperature flexibility [4] and appropriate mechanical properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 It has been used in several industries such as automotive, construction, electrical, and sealing applications. 15,16 However, like many rubber materials, EPDM is susceptible to oxidative aging, which can lead to a loss of its mechanical strength, changes in physical properties, and reduced service life of EPDM rubber products. 17,18 Therefore, protecting EPDM from oxidative aging is crucial to maintain its performance and longevity in various industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…EPDM rubber is a synthetic rubber with exceptional properties 13,14 . It has been used in several industries such as automotive, construction, electrical, and sealing applications 15,16 . However, like many rubber materials, EPDM is susceptible to oxidative aging, which can lead to a loss of its mechanical strength, changes in physical properties, and reduced service life of EPDM rubber products 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…They have low density and good thermal, and mechanical properties. 4,5 Ethylene propylene diene monomer (EPDM) is one of the most important elastomeric materials used for SRM's internal thermal insulations. 6,7 Extensive research has revealed that the integrity of the char layer produced through the pyrolysis of carbonized insulation material plays a pivotal role in determining its longterm ablation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Elastomers are reliable polymeric composites with a wide range of applications in the automotive industry, thermal insulation, manufacturing, etc. They have low density and good thermal, and mechanical properties 4,5 . Ethylene propylene diene monomer (EPDM) is one of the most important elastomeric materials used for SRM's internal thermal insulations 6,7 .…”
Section: Introductionmentioning
confidence: 99%